2003
DOI: 10.1177/07419325030240050201
|View full text |Cite
|
Sign up to set email alerts
|

Access to the General Curriculum of Middle School Students with Mental Retardation

Abstract: The IDEA requires participation and progress in the general curriculum by all students. However, there is limited knowledge about the degree to which students with mental retardation have such access. This study examined the degree to which middle school students with mental retardation have access to the general curriculum and the impact of the classroom setting and the student's level of ability on such access. Findings indicated that students with mental retardation were most likely to participate with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
133
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 1 publication
13
133
1
3
Order By: Relevance
“…First, the sample size was relatively small (n = 19) and thus presents problems for generalization. Given, however, the congruence between our findings and those of Wehmeyer et al (2003), we believe that these findings are not outside tbe norm as tbey relate to tbe issue of access to the general education curriculum for students with intellectual disabilities. Second, several students in the study were caught by the same teacher during their respective observations.…”
Section: Limitations Of Studymentioning
confidence: 54%
See 3 more Smart Citations
“…First, the sample size was relatively small (n = 19) and thus presents problems for generalization. Given, however, the congruence between our findings and those of Wehmeyer et al (2003), we believe that these findings are not outside tbe norm as tbey relate to tbe issue of access to the general education curriculum for students with intellectual disabilities. Second, several students in the study were caught by the same teacher during their respective observations.…”
Section: Limitations Of Studymentioning
confidence: 54%
“…As noted previously, Wehmeyer et al (2003) found that students receiving their education in general education settings had greater access to the general education curriculum. Similarly, found that students with severe disabilities educated in general education classrooms received more academically focused instruction than students with severe disabilities who were educated in self-contained classrooms.…”
Section: Practitioners Often Interpret Promoting "Access To Thementioning
confidence: 62%
See 2 more Smart Citations
“…With regard to students with special needs/ disabilities many research studies in differentiated instruction report a lack of curriculum modifications in mainstream classrooms for these students (Buckley, 2005;Strogilos & Stefanidis, 2015;Strogilos, Tragoulia, & Kaila, 2015), and consequently, according to Scruggs, et al's (2007) literature review, the education of these students in general classrooms lacks appropriate teaching materials, differentiation in activities and opportunities for individualizing the curriculum. Similarly, Wehmeyer, Lattin, Lapp-Rincker, and Agran (2003) indicated that teachers were adapting their materials in less than 3% of their observations for students with intellectual disabilities. Also, Strogilos, Tragoulia, and Kaila (2015) identified limited curriculum modifications for students with SEN in their descriptive observations in mainstream classrooms.…”
Section: Research Findings On Differentiated Instructionmentioning
confidence: 99%